PEMETAAN POTENSI BIOGAS DI KOTA METRO - Riswanto Riswanto (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
Metro City is a developing city that attracts many new citizens to come and live in the city of Metro. It affects the density and population growth in the city of Metro so it boils down to the increasing need for energy for fuel such as gas and electricity needs. UU No. 33 of 2007 the government seeks to optimize the role of PEMDA and communities and academics to be able to take advantage of the various potential that may be developed in their respective city in meeting energy needs. The survey results show the picture that the city of Metro has potential in the utilization of biogas energy. The availability of this organic material is quite common in Metro city. But the availability of the material has not been classified in number and variety. For that, we need to do research in mapping biogas potential in every area in Metro city. The research method used is the method of documentation, observation, and interview. As for data analysis techniques, conducted qualitatively and quantitatively through the findings of observations in the form of descriptions, calculation analysis, and tabulation. The results obtained show that the North Metro sub-district has the highest potential for biogas development. The most common materials are animal waste derived from cow dung as much as 84% and biogas from plants that are from rice straw (54%) and Tahu/tempe processing waste (38%). Other organic ingredients found are chicken, goat, buffalo, and banana peels. This result shows that the biogas potency of Metro City is best developed that is through the use of cow dung